DIFFERENTIATION AND INTEGRATION IN SPORT SCIENCE, ROLE AND TASK OF INTERDISCIPLINARY SPORT SCIENCE - Andras S. Szabo; Pal Tolnay (Sport Scientific And Practical Aspects, 2025)
The article deals with questions of differentiation and integration of sport science. Analysing some special fields of sport science the auhors try to find true answers to the following questions: - do we have a really independent (individual) sport science? - is the sport science an interdisciplinary one? - what are the development trends and tendencies in sport science (quo vadis sport science)? - what are the dominant contradictions and other serious problems of the sport and sportscience in the XXI century?